2010
DOI: 10.1080/07347330903438958
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Investigation of Coping and Posttraumatic Growth in Breast Cancer Survivors

Abstract: This study supported several predictions for coping and distress during chemotherapy (Time 1), and coping, perceived stress, and posttraumatic growth two years later (Time 2) in women with breast cancer. At T1, the emotion-focused coping strategies of disengagement, denial, self-blame, and venting were positively related to physical and psychological distress. In addition, the cognitive strategies of religion, positive reframing, and acceptance together accounted for a significant amount of the variance in fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
97
2
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(121 citation statements)
references
References 42 publications
12
97
2
10
Order By: Relevance
“…Our results are in accordance with the previous literature [12,14,15]. Past research suggest that denial, self-blame, disengagement and venting were positively related to psychological distress while planning, acceptance, positive reframing and religious coping are associated with growth.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in accordance with the previous literature [12,14,15]. Past research suggest that denial, self-blame, disengagement and venting were positively related to psychological distress while planning, acceptance, positive reframing and religious coping are associated with growth.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, negative religious coping was associated with distress and positive religious coping was associated with PTG [13] besides, emotion-focused coping strategies of denial, self-blame, disengagement and venting were positively related to psychological distress [14] while substance use was related to less PTG [15]. In another review [16], it was demonstrated that growth was associated with depression, positive reappraisal, spirituality, and religious coping.…”
Section: Introductionmentioning
confidence: 99%
“…An active style of coping with disease also yields positive outcomes [38,39]. The average score in this area in the study group was 43.31.…”
Section: Discussionmentioning
confidence: 90%
“…Optimism (Bostock et al, 2009;Ho et al, 2010), hope (Ai, Cascio, Santangelo & Evans-Campbell, 2005;Ho et al, 2010), spirituality or certain religious beliefs (Ai et al, 2005;Cadell, Regehr & Hemsworth, 2003;Thombre, Sherman & Simonton, 2010), extraversion (Tedeschi & Calhoun, 1996), as well as a problem-focused coping (Bussell & Naus, 2010;Dirik & Karanci, 2008), are some features that most commonly have been associated to a high likelihood of PTG. It is generally assumed that most of the empirical evidence on the existence of PTG has been based from single-case studies with exceptionally mentally-strong or extraordinary people (Masten, 2001).…”
Section: Post-traumatic Stress Disorder (Ptsd) and Posttraumatic Growmentioning
confidence: 99%